2017
DOI: 10.1002/ppsc.201700258
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enhanced Emission of Visible Light from Core–Dual‐Shell‐Type Hybridized Nanoparticles

Abstract: Core–dual‐shell‐type hybridized nanoparticles (NPs) having Au‐core/dye‐doped silica inner shell/Au outer shell are successfully fabricated by developing a biphasic process that is a kind of so‐called “one‐pot” method. The resulting hybridized NPs exhibit evidently about 20‐fold enhancement of fluorescence intensity, increase in fluorescence quantum yield, and decrease in fluorescence lifetime. These effects depend on the metal nanostructure being optimized, compared with the reference hybridized NPs with neith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Multilayered spherical nanoparticles are fundamental building blocks for many vital applications in physics and chemistry: tailored scattering [1][2][3][4][5][6][7] and nonlinear optics [1,2,8,9], photonic crystals [10][11][12][13][14], sensing [15][16][17], photothermal cancer treatment [18][19][20][21], solar energy harvesting [22,23], photovoltaics [24], fluorescence [25][26][27][28][29][30], photoluminescence [31] and upconversion [32][33][34][35][36][37][38][39][40] enhancement, surface-enhanced Raman scattering (SERS) [25,41,42], surface plasmon amplification by stimulated emission of radiation (spaser) [43][44][45]...…”
Section: Introductionmentioning
confidence: 99%
“…Multilayered spherical nanoparticles are fundamental building blocks for many vital applications in physics and chemistry: tailored scattering [1][2][3][4][5][6][7] and nonlinear optics [1,2,8,9], photonic crystals [10][11][12][13][14], sensing [15][16][17], photothermal cancer treatment [18][19][20][21], solar energy harvesting [22,23], photovoltaics [24], fluorescence [25][26][27][28][29][30], photoluminescence [31] and upconversion [32][33][34][35][36][37][38][39][40] enhancement, surface-enhanced Raman scattering (SERS) [25,41,42], surface plasmon amplification by stimulated emission of radiation (spaser) [43][44][45]...…”
Section: Introductionmentioning
confidence: 99%
“…The solution of this problem implies the definition of the electromagnetic field within or outside of a sphere which allows to get its absorption, scattering, extinction or other important characteristics. Among these properties, the cycle-and orientation-averaged electric |E| 2 and magnetic |H| 2 fields (in general, electromagnetic energy) within a particular layer (shell) or in the vicinity of a multilayered sphere is of great importance since it defines performance and suitability of a multilayered sphere for a large number of intriguing applications: nonlinear optics [17][18][19], lasing [20][21][22], heating [23][24][25], photocatalysis [26], fluorescence enhancement [27][28][29][30], plasmon-enhanced upconversion [31,32], energy harvesting and storing [33][34][35][36], surface-enhanced Raman spectroscopy [37][38][39], biology and medicine [40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Isotropic emission derived from spherical structures has been investigated as a means of obtaining SPASER systems. Ayala‐Orozco et al demonstrated FL enhancement in the near‐infrared by preparing nanomatryoshka and Sakamoto et al reported enhanced emission in the visible range from Au‐core/dye‐SiO 2 /Au dual shell NPs . It is noteworthy that structural asymmetry should induce stronger FL emissions than are obtained from symmetric configurations based on the theory of energy equipartition …”
Section: Introductionmentioning
confidence: 99%
“…Ayala-Orozco et al demonstrated FL enhancement in the near-infrared by preparing nanomatryoshka [40] and Sakamoto et al reported enhanced emission in the visible range from Au-core/dye-SiO 2 /Au dual shell NPs. [41] It is noteworthy that structural asymmetry should induce stronger FL emissions than are obtained from symmetric configurations based on the theory of energy equipartition. [42] In the present study, Janus particles were prepared with a fluorescent dye and Au NPs on one side.…”
Section: Introductionmentioning
confidence: 99%